Analisis Potensi dan Efektivitas Pajak Parkir serta Kontribusinya terhadap Penerimaan Pajak Daerah Kota Banjarmasin - Muhammad Prawira Oktariani; Muzdalifah Muzdalifah (PPJP Universitas Lambung Mangkurat, 2023)
The purpose of this study is to (1) know the amount of potential parking tax in Banjarmasin City, (2) know the effectiveness of the parking tax in Banjarmasin City, and (3) know the level of parking tax contribution to local tax revenue in Banjarmasin City.This study uses a quantitative descriptive method. The data types used in this study are primary and secondary, with data collection techniques through interviews, observation, documentation, and literature.The study results show that the potential of the Banjarmasin parking tax is greater than the revenue or realization in the previous year. The level of effectiveness of the Banjarmasin City parking tax in 2015-2019 averages 98.19% or is in the effective category. Meanwhile, the parking tax contribution to Banjarmasin City's local tax revenue in 2015-2019 has an average of 2.73% or is in the very poor category.